Organic electronics material, organic layer, organic electronics element, display element, lighting device, and display device
A charge-transporting polymer with a specific arylamine structure addresses the need for cost-effective and efficient conductivity improvement in organic electronic devices by utilizing a Buchwald-Hartwig reaction to form organic layers.
Patent Information
- Application Number
- JP2023113253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
AI Technical Summary
Conventional arylamine polymers used in organic electronic devices require expensive materials and multi-step processes, and there is a demand for charge-transporting polymers that can improve conductivity and form organic layers using inexpensive materials in a simple manner.
Development of a charge-transporting polymer with a specific arylamine structure, represented by formulas (a) and (b), which can be synthesized using a Buchwald-Hartwig reaction with aromatic compounds, allowing for the formation of an organic layer with improved conductivity.
The polymer enables the formation of an organic layer with enhanced conductivity using inexpensive materials and simple methods, suitable for organic electronic devices.
Smart Images

Figure 2025010937000001_ABST
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE The present invention relates to an organic electronic material, an organic layer, an organic electronic element, a display element, a lighting device, and a display device. [Background technology]
[0002] Organic electronics elements are elements that use organic materials to perform electrical functions, and are expected to offer advantages such as energy savings, low cost, and flexibility. As such, they are attracting attention as a technology that can replace conventional silicon-based inorganic semiconductors.
[0003] Examples of organic electronic elements include organic electroluminescence elements (hereinafter referred to as organic EL elements), organic photoelectric conversion elements, and organic transistors. Among organic electronic elements, organic EL elements have been attracting attention as large-area solid-state light sources, for example, as replacements for incandescent lamps and gas-filled lamps. They have also been attracting attention as the most promising self-luminous displays to replace liquid crystal displays (LCDs) in the field of flat panel displays (FPDs), and commercialization is progressing.
[0004] Organic EL elements are broadly classified into low molecular weight organic EL elements and high molecular weight organic EL elements based on the organic materials that compose the element. Low molecular weight organic EL elements use low molecular weight compounds and require a dry process in which a film is formed under vacuum. In contrast, high molecular weight organic EL elements use high molecular weight compounds and can be easily formed into a film using wet processes such as plate printing, including letterpress printing and intaglio printing, and plateless printing, including inkjet printing.
[0005] For this reason, polymer-type organic EL elements that can be easily formed are expected to be essential elements for realizing large-screen organic EL displays in the future. For this reason, in recent years, the development of various charge-transporting polymers as polymer compounds that constitute polymer-type organic EL elements has been progressing. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2008 / 010487 Summary of the Invention [Problem to be solved by the invention]
[0007] As an example of a charge transporting polymer, an arylamine polymer is widely known, and efforts are being made to improve various properties of organic electroluminescence devices by molecular design of the polymer. For example, Patent Document 1 discloses an arylamine polymer containing a triphenylamine structure. However, in recent years, in the field of organic electronics such as organic electroluminescence devices, further improvements in various properties such as electrical conductivity are required, and conventional arylamine polymers have room for improvement. In addition, in order to introduce a specific structure into an arylamine polymer, expensive materials or multi-step processes are often required in the production of the polymer. Therefore, there is a demand for a charge-transporting polymer that can form an organic layer that can improve various properties of an organic electroluminescence device and can be obtained by a simple method using inexpensive materials.
[0008] Thus, one embodiment of the present invention provides an organic electronic material including a charge transporting polymer capable of forming an organic layer capable of improving electrical conductivity and obtained by a simple method using inexpensive materials. Another embodiment of the present invention provides an organic electronic device having excellent electrical conductivity. [Means for solving the problem]
[0009] The present inventors have conducted extensive research into charge transporting polymers having an arylamine structure and have found that polymers having a specific arylamine structure are suitable as organic electronic materials, thereby completing the present invention.
[0010] That is, the embodiments of the present invention relate to the following, but the present invention is not limited to the following embodiments and includes various embodiments.
[0011] [1] An organic electronic material comprising a charge-transporting polymer that includes a trivalent structural unit represented by the following formula (a) and a divalent structural unit represented by the following formula (b), and that has at least a structure represented by the following formula (I) in which at least one bond in the trivalent structural unit and at least one bond in the divalent structural unit are directly bonded to each other, and that has a weight-average molecular weight of 900 to 500,000. [ka] [ka] In the formula, Ar represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.
[0012] [2] The organic electronic material according to the above [1], wherein in the structure represented by formula (I), Ar is a group represented by the following formula: [ka] In the formula, R 1 is an alkyl group having 1 to 8 carbon atoms, and a is 0 or an integer of 1 to 5.
[0013] [3] The organic electronic material according to the above [1] or [2], wherein the structure represented by the above formula (I) includes a structure represented by the following formula (I-2) or (I-3): [ka] In the formula, each Ar independently represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.
[0014] [4] The organic electronic material according to the above [1] or [2], wherein the charge transporting polymer comprises a structure represented by the following formula (IA): [ka] In the formula, Ar represents a substituted or unsubstituted aryl group, and n is an integer of 2 or more.
[0015] [5] The organic electronic material according to any one of the above [1] to [4], wherein the charge transporting polymer further has a monovalent structural unit represented by the following formula (c): [ka] In the formula, R 2 is an alkyl group having 1 to 8 carbon atoms, and b is 0 or an integer of 1 to 5.
[0016] [6] The organic electronic material according to any one of the above [1] to [5], further comprising a solvent.
[0017] [7] An organic layer formed using the organic electronics material described in [6] above.
[0018] [8] An organic electronic device comprising the organic layer according to [7] above.
[0019] [9] An organic electroluminescence device comprising the organic layer according to [7] above.
[0020]
[10] A display device comprising the organic electroluminescence device according to [9] above.
[0021] A lighting device comprising the organic electroluminescence element according to [9] above.
[0022] A display device comprising the lighting device according to
[11] above and a liquid crystal element as a display means. Effect of the Invention
[0023] According to an embodiment of the present invention, it is possible to provide an organic electronic material including a charge transporting polymer capable of forming an organic layer capable of improving electrical conductivity and obtained by a simple method using inexpensive materials. Also, according to another embodiment of the present invention, it is possible to provide an organic electronic element having excellent electrical conductivity. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a cross-sectional view showing an example of an organic EL element according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing the structure of the hole-only device prepared in the example. [Diagram 3] FIG. 3 is a graph showing voltage-current density curves when a voltage was applied to each of the hole-only devices fabricated in Example 5 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the embodiment described below. <1> Organic Electronics Materials (Charge transport polymer) One embodiment of the present invention relates to an organic electronic material. The organic electronic material of this embodiment includes a charge-transporting polymer that contains a trivalent structural unit having charge transportability and a divalent structural unit having charge transportability, has a structure represented by the following formula (I), and has a weight-average molecular weight of 900 to 500,000.
[0026] [ka] In the formula, Ar represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.
[0027] As represented by the above formula (I), the charge transporting polymer is characterized by including a triphenylamine structure and having an N-Ph-N bond in the molecule. The charge transporting polymer has the structure represented by the above formula (I), which makes it easy to dope and conjugate. Therefore, it is considered that the organic layer capable of improving electrical conductivity can be easily formed by using the charge transporting polymer having the structure represented by the above formula (I).
[0028] In the charge transporting polymer, the N-Ph-N bond can be formed, for example, by the reaction of an aromatic compound having an amino group with an aromatic compound having a functional group capable of reacting with an amino group. From this viewpoint, in one embodiment, the charge transporting polymer includes a trivalent structural unit represented by the following formula (a) and a divalent structural unit represented by the following formula (b), and preferably has at least a structure (I) represented by the above formula (I) in which at least one bond in the trivalent structural unit and at least one bond in the divalent structural unit are directly bonded.
[0029] [ka]
[0030] In the formula, Ar represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.
[0031] In the above formula (a), at least one hydrogen atom in the benzene ring of the triphenylamine may be substituted with a substituent R. Each of the substituents R is independently -R 1 , -OR 2 , -SR 3 , -OCOR 4 , -COOR 5 , -SiR 6 R 7 R 8 R 1 ~R 8 Each independently represents a hydrogen atom (R 1(except for the case where R is 1 to 22 carbon atoms); a straight-chain, cyclic or branched alkyl group; or an aryl group or heteroaryl group having 2 to 30 carbon atoms. The aryl group is an atomic group obtained by removing one hydrogen atom from an aromatic hydrocarbon. The heteroaryl group is an atomic group obtained by removing one hydrogen atom from an aromatic heterocycle. The alkyl group may be further substituted with an aryl group or heteroaryl group having 2 to 20 carbon atoms, and the aryl group or heteroaryl group may be further substituted with a straight-chain, cyclic or branched alkyl group having 1 to 22 carbon atoms. The substituent R may preferably be an alkyl group, an aryl group, or an alkyl-substituted aryl group.
[0032] In the above formula (b), the substituted or unsubstituted aryl group represented by Ar may be a group derived from an aromatic compound having 6 to 24 carbon atoms. The above aromatic compound is, for example, an aromatic hydrocarbon, and specific examples thereof include benzene, naphthalene, anthracene, tetracene, fluorene, phenanthrene, biphenyl, terphenyl, and triphenylbenzene. The aromatic ring in the aromatic compound may have one or more substituents. The substituents may be an alkyl group, an aryl group, or an alkyl-substituted aryl group. The alkyl group may be a linear, cyclic, or branched alkyl group having 1 to 22 carbon atoms. The aryl group may have 6 to 20 carbon atoms. The alkyl of the alkyl-substituted aryl group is the same as the above alkyl group.
[0033] In one embodiment, Ar may be a group represented by the following formula (b-1): [ka] R in the above formula (b-1) 1 is an alkyl group having 1 to 8 carbon atoms, and a is 0 or an integer of 1 to 5.
[0034] In one embodiment, R in formula (b-1) 1 R may be a linear, branched, or cyclic alkyl group having 1 to 8 carbon atoms. 1may be preferably a linear or branched alkyl group having 1 to 8 carbon atoms, more preferably a linear or branched alkyl group having 2 to 8 carbon atoms, and even more preferably a linear or branched alkyl group having 4 to 8 carbon atoms. In one embodiment, a may be preferably 0 or 1 to 4, more preferably 1 to 3, and even more preferably 1 or 2.
[0035] (Method of Manufacturing Charge-Transporting Polymer) The charge transporting polymer having the structure represented by the above formula (I) can be produced by a known method using two or more aromatic compounds as monomers, capable of forming a binding site represented by the following formula (i) by a reaction between the two or more monomers.
[0036] [ka]
[0037] In order to produce the charge transporting polymer, for example, an aromatic compound having a reactive functional group X and an aromatic compound having a reactive functional group Y capable of reacting with the reactive functional group X can be used, and a coupling reaction between these compounds can be applied. In one embodiment, the Buchwald-Hartwig reaction can be applied as a method for producing the charge transporting polymer. In the case of the Buchwald-Hartwig reaction, the combination of the reactive functional group X and the reactive functional group Y can be a halogeno group and an amino group. The amino group is preferably a primary amino group.
[0038] In the above embodiment, the charge transporting polymer can be obtained by reacting an aromatic compound having a halogen atom directly bonded to the aromatic ring with an aromatic compound having a primary amino group according to a known method using the Buchwald-Hartwig reaction. Here, the halogen atom can be a chlorine atom, a bromine atom, or an iodine atom. In another embodiment, an aromatic compound having a triflate group instead of a halogen atom can also be used.
[0039] In the Buchwald-Hartwig reaction, an aromatic compound (1) having two or more halogen atoms or triflate groups directly bonded to an aromatic ring and an aromatic compound (2) having a primary amino group are used to produce an arylamine polymer having one or more structural units derived from each of the aromatic compound (1) and the aromatic compound (2). From this viewpoint, by selecting an aromatic compound to be used as a raw material monomer, a charge transporting polymer having two or more structures represented by the desired formula (I) (hereinafter also referred to as structure (I)) as represented by the following formula (IA) can be easily obtained.
[0040] [ka] In the formula, Ar represents a substituted or unsubstituted aryl group, and n is an integer of 2 or more. n may be preferably 3 or more, more preferably 5 or more, and further preferably 10 or more. For example, n may be an integer appropriately set so that the weight average molecular weight (Mw) of the charge transporting polymer is in the range of 900 to 500,000, 2,000 to 500,000, 3,000 to 500,000, or 5,000 to 300,000.
[0041] In one embodiment, at least a triphenylamine having a halogen atom and an arylamine can be used as a raw material monomer for producing a charge transporting polymer. In such an embodiment, the structure (I) in the charge transporting polymer preferably includes a structure represented by the following formula (I-2) or the following formula (I-3).
[0042] [ka] In the formula, Ar represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.
[0043] From the viewpoint of obtaining a charge transporting polymer having a structure represented by the above formula (I-1) or the above formula (I-2), in one embodiment, at least triphenylamine having three halogen atoms directly bonded to an aromatic ring and arylamine can be suitably used as raw material monomers. More specifically, a compound having a halogen atom directly bonded to each of the three bonds of a trivalent structural unit represented by the above formula (a) and a compound having a hydrogen atom bonded to two bonds of a divalent structural unit represented by the above formula (b) can be suitably used.
[0044] In one embodiment, the charge transporting polymer may further have a monovalent structural unit represented by the following formula (c):
[0045] [ka] In the formula, R 2 is an alkyl group having 1 to 8 carbon atoms, and b is 0 or an integer of 1 to 5.
[0046] In one embodiment, R 2 R may be a linear, branched, or cyclic alkyl group having 1 to 8 carbon atoms. 2 may be preferably a linear alkyl group having 1 to 8 carbon atoms, more preferably a linear alkyl group having 2 to 8 carbon atoms, and even more preferably a linear alkyl group having 3 to 8 carbon atoms. In one embodiment, b may be preferably 0 or 1 to 4, more preferably 1 to 3, and even more preferably 1 or 2.
[0047] In one embodiment, in order to introduce the structural unit (c) into the charge transporting polymer, a compound in which a halogen atom is directly bonded to a bond in the structural unit (c) can be used as a raw material monomer.
[0048] In one embodiment, the charge transporting polymer may further include other structural units in addition to the above structural units (a), (b), and (c). In this case, a charge transporting polymer having a desired structure can be easily obtained by using an aromatic compound having a halogen atom or an amino group capable of inducing the additional structural unit.
[0049] The weight average molecular weight (Mw) of the charge transporting polymer is not particularly limited, but may be 900 or more. From the viewpoint of film-forming property, the Mw is preferably 2,000 or more, more preferably 3,000 or more, even more preferably 5,000 or more, and particularly preferably 10,000 or more. Moreover, the Mw is preferably 500,000 or less, more preferably 300,000 or less, and even more preferably 150,000 or less. When the polymer has an Mw in the above range, it has excellent charge transport property, and can be suitably used as an organic electronics material. In addition, it is also preferable in that it has excellent solubility in a solvent used to prepare a coating liquid and excellent film-forming property can be obtained.
[0050] The Buchwald-Hartwig reaction can be carried out according to conditions and methods well known to those skilled in the art. For example, the reaction can be carried out under an inert gas atmosphere such as nitrogen, using a compound containing a heavy metal such as palladium as a catalyst. It is preferable to use a catalyst and a base in combination during the reaction.
[0051] In the Buchwald-Hartwig reaction, a palladium-containing catalyst can be preferably used as a catalyst. In this specification, the term "palladium-containing catalyst" refers to a catalyst containing palladium and a ligand, and includes a complex compound or salt containing palladium and a ligand, or a combination of a precursor of the palladium-containing catalyst and a ligand or a ligand precursor.
[0052] The above-mentioned ligand is preferably one having a bulky structure, and specific examples thereof include phosphine ligands and Buchwald ligands. N-heterocyclic carbene (NHC) can also be used as the ligand. Among them, phosphine ligands such as tri-t-butylphosphine, tri-o-tolylphosphine, and triphenylphosphine are more preferred.
[0053] The palladium-containing catalyst may be a palladium(0) complex or a palladium(II) salt. Specific examples of palladium-containing catalysts include bis(tri-t-butylphosphine)palladium(0), tetrakis(triphenylphosphine)palladium(0), bis[1,2-bis(diphenylphosphino)ethane]palladium(0), dichlorobis(triphenylphosphine)palladium(II), dichlorobis(tri-o-tolylphosphine)palladium(II), bis[di-t-butyl(4-dimethylaminophenyl)phosphine]dichloropalladium(II), [1,1'-bis(di-t-butylphosphino)ferrocene]dichloropalladium(II), dichloro[1,1'-bis(diphenylphosphino)ferrocene]palladium(II), dichloro[1,2-bis(diphenylphosphino)ethane]palladium(II), and dichloro[1,3-bis(diphenylphosphino)propane]palladium(II), and Umicore CX31 and CX32 having NHC ligands. These compounds can also be used in combination with the ligands or ligand precursors described above.
[0054] Also, a precursor of a palladium-containing catalyst can be used to generate active palladium in the reaction system from the precursor, using organometallic reagents, phosphines, amines, and other components present in the reaction system. Examples of the precursor include bis(dibenzylideneacetone)palladium(0), palladium acetate(II), palladium chloride(II), di-μ-chlorobis[(η-allyl)palladium(II)], dichlorobis(acetonitrile)palladium(II), and dichlorobis(benzonitrile)palladium(II).
[0055] When using the precursor of the above-mentioned palladium-containing catalyst, it is preferable to use a precursor of a ligand such as a triphosphonium salt in combination. A specific example of the triphosphonium salt is tri-t-butylphosphonium tetrafluoroborate. This compound generates tri-t-butylphosphine in the system and functions as a ligand for palladium. Although not particularly limited, in one embodiment, it is preferable to use a combination of bis(tri-t-butylphosphine)palladium(0) and tri-t-butylphosphonium tetrafluoroborate as the palladium-containing catalyst.
[0056] In one embodiment, a palladium-containing catalyst having at least a structure represented by the following formula (1) can be suitably used as the catalyst. PdArBrP(t-Bu)3(1)
[0057] In the formula, Ar is a substituted or unsubstituted aryl group having 6 to 30 carbon atoms. Ar may be, for example, a substituted or unsubstituted phenyl group. At least one hydrogen atom in the aromatic ring of the aryl group may be substituted with an alkyl group having 1 to 12 carbon atoms.
[0058] A specific example of the palladium-containing catalyst having the above structure is the compound represented by the following formula (2): This compound can be produced, for example, by reacting tris(dibenzylideneacetone)dipalladium(0), o-bromotoluene, and tri-tert-butylphosphine. [ka]
[0059] In another embodiment, a palladium-containing catalyst having at least a structure represented by the following formula can be suitably used as the catalyst. [ka]
[0060] In the formula, R represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. L represents a ligand. Z represents a leaving group. The leaving group may be one selected from the group consisting of a halogen atom, a methylsulfonyloxy group (-OSO2CH3), a tosyl group (-OSO2C6H5CH3), and a trifluoromethylsulfonyloxy group (-OSO2CH3).
[0061] Specific examples of the catalyst having the structure represented by the above formula (3) include the following. [ka]
[0062] In one embodiment, the palladium-containing catalyst that can be suitably used can be produced according to a known method, but can also be obtained as a commercial product. For example, the XphosPd series manufactured by Aldrich Co., Ltd. can be used, and among them, the catalysts represented by the above formulas (3-1) to (3-4) can be obtained as XphosPd G1, XphosPd G2, XphosPd G3, and XphosPd G4. In one embodiment, the catalysts represented by the above formulas (3-2) and (3-4) can be more preferably used, and these can be obtained as XphosPd G2 and XphosPd G4, respectively.
[0063] The amount of the catalyst used is not particularly limited, but may typically be in the range of 0.1 mol% or more and 20 mol% or less with respect to the aromatic compound having an amino group used as the raw material monomer. By adjusting the amount of the catalyst used within the above range, it becomes easy to efficiently proceed with the reaction and to suppress the generation of by-products. In one embodiment, the amount of the catalyst used may be preferably 0.1 mol% to 10 mol%, more preferably 0.1 mol% to 5 mol%, and even more preferably 0.1 mol% to 2 mol%, with respect to the aromatic compound having an amino group used as the raw material monomer. According to the production method of this embodiment, even if the amount of the catalyst used is reduced, it is possible to efficiently proceed with the reaction. Therefore, it becomes easy to reduce the amount of impurities derived from the catalyst in the polymer obtained by the reaction.
[0064] In one embodiment, the palladium-containing catalyst may further include an additive. The additive is preferably a compound that functions as a ligand for palladium metal. Specific examples of compounds that can be used as additives include P(t-Bu)3·HBF3, PCy3·HBF3, and Xphos (2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl). Among these, P(t-Bu)3·HBF3 is preferred. When such an additive is used, the reactivity of the palladium catalyst tends to be further improved.
[0065] The base is not particularly limited, and may be either an inorganic base or an organic base. In one embodiment, although not particularly limited, an organic base is preferred, and an organic alkali metal compound such as t-butoxy sodium or n-butyl lithium can be suitably used. The amount of the base used is not particularly limited, but may typically be in the range of 1.0 molar equivalent or more and 4 molar equivalent or less with respect to the number of moles of the aromatic compound having an amino group used as the raw material monomer. By adjusting the amount of the base used within the above range, the reaction can be efficiently carried out and the production of by-products can be easily suppressed.
[0066] The reaction is preferably carried out in the presence of an organic solvent. Examples of the organic solvent (reaction solvent) include aromatic hydrocarbons such as benzene and toluene, aliphatic ethers such as dioxane, tetrahydrofuran, and dimethoxyethane, amide solvents such as N,N-dimethylformamide and N,N-dimethylacetamide, and dimethylsulfoxide. Among them, in one embodiment, the reaction is preferably carried out in the presence of an aromatic hydrocarbon, and more preferably in the presence of toluene.
[0067] The reaction temperature is not particularly limited. For example, the reaction temperature may be in the range of 0 to 200° C. In one embodiment, the reaction temperature is preferably in the range of 80 to 180° C.
[0068] In the mixture of raw material monomers, the blending ratio of the aromatic compound having an amino group and the aromatic compound having a halogen atom is not particularly limited.However, if the unreacted raw material monomers remain in excess in the reaction system, undesirable side reactions may occur, so it is preferable to adjust the blending ratio appropriately.The blending ratio can be adjusted appropriately in consideration of the structure of the aromatic compound used as raw material monomer and the structure of the desired charge transport polymer.
[0069] In one embodiment of the charge transporting polymer, for example, a trihalogenated aromatic compound and a primary monoamine can be used as the raw material monomer, more specifically, a tri(halogenophenyl)amine and an aniline can be used. The tri(halogenophenyl)amine can be tri(4-chlorophenyl)amine, tri(4-bromophenyl)amine, tri(4-iodophenyl)amine, etc. More specifically, the following compounds can be suitably used. That is, the raw material monomer may be a monomer mixture of a trihalogenated aromatic compound containing an aromatic compound represented by the following formula (A) and an arylamine containing an aromatic compound represented by the following formula (B). The aromatic compound represented by the following formula (B) has a substituent R 1In the structure represented by the following formula (B), the substituent R 1 , a is as explained above in formula (b-1).
[0070] [ka]
[0071] In one embodiment, the monomer mixture may further include a monohalogenated aromatic compound in which one of the hydrogen atoms in the aromatic ring is replaced with a halogen atom. For example, the monomer mixture may further include a monohalogenobenzene. Examples of the monohalogenobenzene include chlorobenzene, bromobenzene, and iodobenzene. It is preferable to include an aromatic compound represented by the following formula (C) as the monohalogenobenzene. The aromatic compound represented by the following formula (C) may have at least one substituent on the aromatic ring. The substituent is as described above with respect to R in the above formula (c). 2 As explained above.
[0072] [ka]
[0073] In one embodiment, it is preferable to use an aromatic compound (A) represented by the above formula (A) and an aromatic compound (B) represented by the above formula (B) as the raw material monomers. The compounding ratio of the raw material monomers (A):(B) may be preferably 0.5 to 1.5:1.0, more preferably 0.6 to 1.4:1.0, as the ratio of the number of reaction points based on the amino group of the aromatic compound (B).
[0074] In one embodiment, in addition to the aromatic compound (A) and aromatic compound (B), an aromatic compound (C) represented by the above formula (C) may be used as the raw material monomer. The compounding ratio of the raw material monomers (A):(B):(C) may be preferably 0.2-0.9:1.0:0.0-1.0, more preferably 0.3-0.7:1.0:0.1-0.9, and even more preferably 0.4-0.6:1.0:0.2-0.8, as a ratio of the number of reaction points based on the amino group of the aromatic compound (B).
[0075] In one embodiment, the charge transporting polymer may further include other structural units in addition to the structural units derived from the aromatic compounds (A), (B), and (C). For example, the charge transporting polymer may further include a divalent structural unit L2 having a structure different from the divalent structural unit L1 derived from the aromatic compound (B). The structural unit L2 may be introduced, for example, using a compound represented by the following formula: Q-L2―Q (B1-1) Ar 1 -NH-L2-NH-Ar 1 (B1-2) In the formula, Q represents a halogen atom and may be, for example, a chlorine atom, a bromine atom, or an iodine atom. L2 represents a divalent organic group derived from an aromatic hydrocarbon or aromatic heterocycle having 2 to 30 carbon atoms, or a triarylamine. In one embodiment, L2 is preferably a divalent organic group derived from a triarylamine, and more preferably a divalent organic group derived from a triphenylamine. Ar 1 may be a monovalent organic group derived from an aromatic compound having 6 to 24 carbon atoms, and preferably has, for example, the structure represented by the above formula (b-1) explained above.
[0076] From the viewpoint of easily producing a preferred charge transporting polymer, the raw material monomer preferably contains the aromatic compound (A), the aromatic compound (B), and the aromatic compound (C), although this is not particularly limited. In one embodiment, the raw material monomer is preferably a mixture consisting of only the aromatic compound (A), the aromatic compound (B), and the aromatic compound (C). When such a mixture is used as the raw material monomer, -(NAr-Ph) is formed without forming a -Ph-Ph- bond in the molecule. n It becomes possible to easily form a polymer having a -(n is an integer of 2 or more) structure.
[0077] As shown above, -(NAr-Ph) n Charge transporting polymers having the structure of - can be easily synthesized according to the Buchwald-Hartwig reaction. On the other hand, impurities derived from the catalyst and raw monomers used in the reaction are likely to remain in the polymer obtained by the above reaction. Therefore, it is preferable to separate and purify the polymer after the above reaction. The separation and purification of the polymer can be performed by applying a method well known in the art. For example, a method can be applied in which water is added to the reaction liquid after the reaction and mixed, the mixture is separated into an organic phase and an aqueous phase, and the polymer is recovered from the organic phase.
[0078] In one embodiment, impurities derived from the catalyst or the like can be more effectively removed by adding a heavy metal trapping agent during the above mixing. The heavy metal trapping agent may be a compound capable of trapping a heavy metal such as palladium used as a catalyst by chelating it, or a compound capable of specifically binding to and adsorbing a heavy metal. For example, a dithiocarbamate can be used. In particular, an aqueous solution of an alkyldithiocarbamate having an alkyl group having 1 to 6 carbon atoms can be preferably used. In addition, the amount of impurities remaining in the polymer obtained by the above production method can be easily reduced by appropriately selecting an organic solvent used during separation and purification. For example, a water-soluble organic solvent such as methanol can be preferably used during mixing of the reaction liquid with water.
[0079] When forming an organic electronic material containing a charge transporting polymer, the charge transporting polymer may contain impurities that are mixed in during the manufacturing process. However, since impurities are a cause of deterioration of the characteristics of an organic electronic element formed using an organic electronic material, it is desirable that the amount of impurities is as small as possible. In one embodiment, from the viewpoint of providing a charge transporting polymer that can be suitably used as an organic electronic material, the palladium content in the polymer is preferably 100 ppm or less, more preferably 80 ppm or less, and even more preferably 50 ppm or less. In addition, the content (total amount) of halogen atoms in the polymer is preferably 300 ppm or less, more preferably 100 ppm or less, and even more preferably 60 ppm or less. As described above, by performing separation and purification as necessary after the coupling reaction, a charge transporting polymer having a desired purity can be easily obtained.
[0080] The organic electronic material according to one embodiment of the present invention comprises at least one charge transporting polymer, including a charge transporting polymer having the above structure (I). The content of the charge transporting polymer in the organic electronic material may be preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, based on the total mass of the organic electronic material. When the content of the charge transporting polymer is adjusted within the above range, excellent charge transportability can be easily obtained. In one embodiment, the content of the charge transporting polymer may be 100% by mass.
[0081] <Other ingredients> The organic electronic material may contain any additive, for example, a dopant. When an additive such as a dopant is used, the content of the charge transporting polymer based on the total mass of the organic electronic material may be 95% or less, or may be 90% or less by mass.
[0082] (Dopant) The dopant is not particularly limited as long as it can exert a doping effect by adding it to an organic electronic material and improve the transportability of charges. There are p-type doping and n-type doping. In p-type doping, a substance that acts as an electron acceptor is used as a dopant, and in n-type doping, a substance that acts as an electron donor is used as a dopant. It is preferable to perform p-type doping to improve hole transportability, and n-type doping to improve electron transportability. The dopant used in the charge transport material may be a dopant that exerts either the effect of p-type doping or n-type doping. In addition, one type of dopant may be added alone, or a mixture of multiple types of dopants may be added.
[0083] The dopant used in p-type doping is an electron-accepting compound, and examples thereof include Lewis acids, protonic acids, transition metal compounds, ionic compounds, halogen compounds, and π-conjugated compounds. Specifically, Lewis acids include FeCl3, PF5, AsF5, SbF5, BF5, BCl3, BBr3, etc.; protonic acids include inorganic acids such as HF, HCl, HBr, HNO3, H2SO4, HClO4, etc., and organic acids such as benzenesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, polyvinylsulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, trifluoroacetic acid, 1-butanesulfonic acid, vinylphenylsulfonic acid, camphorsulfonic acid, etc.; transition metal compounds include FeOCl, TiCl4, ZrCl4, HfCl4, NbF5, AlCl3, NbCl5, TaCl5, MoF5; ionic compounds include tetrakis(pentafluorophenyl)borate ion, tris(trifluoromethanesulfonyl)methide ion, bis(trifluoromethanesulfonyl)imide ion, hexafluoroantimonate ion, AsF6 - (Hexafluoroarsenate ion), BF4 - (Tetrafluoroborate ion), PF6 -(hexafluorophosphate ion) and other perfluoro anions, salts having the conjugate base of the protonic acid as an anion, etc.; halogen compounds include Cl2, Br2, I2, ICL, ICL3, IBR, IF, etc.; π-conjugated compounds include TCNE (tetracyanoethylene), TCNQ (tetracyanoquinodimethane), etc. It is also possible to use known electron-accepting compounds other than those mentioned above. Preferred are Lewis acids, ionic compounds, π-conjugated compounds, etc. Ionic compounds also function as polymerization initiators.
[0084] The dopant used in n-type doping is an electron-donating compound, and examples thereof include alkali metals such as Li and Cs, alkaline earth metals such as Mg and Ca, salts of alkali metals such as LiF and Cs2CO3, and / or alkaline earth metals, metal complexes, and electron-donating organic compounds.
[0085] The content of the dopant is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more, based on the total mass of the organic electronic material. On the other hand, from the viewpoint of maintaining good film formability, the content of the dopant is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, based on the total mass of the organic electronic material.
[0086] In another embodiment, the organic electronic material may further contain other additives from the viewpoint of improving the workability when forming an organic layer as an ink composition, further improving the function of the organic layer, etc. Examples of the other additives include a polymerization inhibitor, a stabilizer, a thickener, a gelling agent, a flame retardant, an antioxidant, a reducing agent, an oxidizing agent, a reducing agent, a surface modifier, an emulsifier, an antifoaming agent, a dispersing agent, a surfactant, etc.
[0087] (solvent) From the viewpoint of applying a wet process as a film formation method, it is preferable that the organic electronic material further contains a solvent. The solvent to be used may be any solvent capable of dissolving the charge transporting polymer. By using an ink composition in which the charge transporting polymer is dissolved in a solvent, an organic layer can be easily formed by a simple method such as a wet process.
[0088] As the solvent, any solvent medium can be used, such as water, an organic solvent, or a mixture thereof. As the organic solvent, alcohols such as methanol, ethanol, isopropyl alcohol, etc.; alkanes such as pentane, hexane, octane, etc.; cyclic alkanes such as cyclohexane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, mesitylene, tetralin, diphenylmethane, etc.; aliphatic ethers such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol-1-monomethyl ether acetate, etc.; 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, anisole, phenetole, 2-methoxytoluene, 3-methylphenyl ether, etc.; Examples of the solvent include aromatic ethers such as methoxytoluene, 4-methoxytoluene, 3-phenoxytoluene, 2,3-dimethylanisole, and 2,4-dimethylanisole; aliphatic esters such as ethyl acetate, n-butyl acetate, ethyl lactate, and n-butyl lactate; aromatic esters such as phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, propyl benzoate, and n-butyl benzoate; amides such as N,N-dimethylformamide and N,N-dimethylacetamide; dimethyl sulfoxide, tetrahydrofuran, acetone, chloroform, and methylene chloride. Preferred are aromatic hydrocarbons, aliphatic esters, aromatic esters, aliphatic ethers, and aromatic ethers, and more preferred are aromatic hydrocarbons.
[0089] The content of the solvent in the organic electronic material (ink composition) can be determined in consideration of application to various coating methods. For example, the content of the solvent is preferably such that the ratio of the charge transport polymer to the solvent is 0.1% by mass or more, more preferably such that the ratio is 0.2% by mass or more, and even more preferably such that the ratio is 0.5% by mass or more. The content of the solvent is preferably such that the ratio of the charge transport polymer to the solvent is 20% by mass or less, more preferably such that the ratio is 15% by mass or less, and even more preferably such that the ratio is 10% by mass or less.
[0090] <2> organic layer One embodiment of the present invention relates to an organic layer formed using the organic electronics material or ink composition. The organic layer exhibits good charge transport properties. By using the ink composition, an organic layer can be formed well and easily by a coating method. Examples of the coating method include known methods such as spin coating; casting; immersion; plate printing methods such as letterpress printing, intaglio printing, offset printing, lithographic printing, letterpress reverse offset printing, screen printing, and gravure printing; and plateless printing methods such as inkjet printing. When the organic layer is formed by a coating method, the coating layer obtained after coating may be dried by heat treatment to remove the solvent.
[0091] The heat treatment can be carried out in an air atmosphere or an inert gas atmosphere. Examples of the inert gas include helium gas, argon gas, nitrogen gas, and mixtures thereof. The "inert gas atmosphere" is preferably an atmosphere in which the concentration of the inert gas is 99.5% or more by volume, more preferably 99.9% or more, and even more preferably 99.99% or more.
[0092] The heat treatment can be carried out using a heater such as a hot plate, an oven, etc. To carry out the heat treatment in an inert gas atmosphere, for example, a hot plate is used in an inert gas atmosphere, or the inside of an oven is made to be under an inert gas atmosphere.
[0093] From the viewpoint of efficiently removing the solvent, the heat treatment is preferably performed at a temperature equal to or higher than the boiling point of the solvent. In addition, when the polymerization reaction of the charge transporting polymer is to proceed, the temperature at which the polymerization reaction proceeds efficiently is preferable. In one embodiment, the temperature of the heat treatment is preferably 140°C or higher, more preferably 180°C or higher, and even more preferably 190°C or higher. On the other hand, from the viewpoint of suppressing deterioration due to the heat treatment, the temperature is preferably 300°C or lower, more preferably 280°C or lower, and even more preferably 250°C or lower.
[0094] The thickness of the organic layer after drying is preferably 0.1 nm or more, more preferably 1 nm or more, and even more preferably 3 nm or more, from the viewpoint of improving the efficiency of charge transport, and is preferably 300 nm or less, more preferably 200 nm or less, and even more preferably 100 nm or less, from the viewpoint of reducing the electrical resistance.
[0095] <3> Organic Electronics Devices One embodiment of the present invention relates to an organic electronics element having at least one of the organic layers. Examples of the organic electronics element include an organic EL element, an organic photoelectric conversion element, and an organic transistor. The organic electronics element preferably has a structure in which an organic layer is disposed between at least a pair of electrodes. The organic electronics element can be manufactured by a manufacturing method including forming an organic layer using the organic electronic material or the ink composition.
[0096] <4> Organic EL element One embodiment of the present invention relates to an organic EL device having at least one of the organic layers. The organic EL device usually comprises an emitting layer, an anode, a cathode, and a substrate, and, if necessary, comprises other functional layers such as a hole injection layer, an electron injection layer, a hole transport layer, and an electron transport layer. Each layer may be formed by a deposition method or a coating method. The organic EL device preferably comprises the organic layer as an emitting layer or another functional layer, more preferably as another functional layer, and further preferably as at least one of a hole injection layer and a hole transport layer.
[0097] Fig. 1 is a cross-sectional schematic diagram showing one embodiment of an organic EL element. The organic EL element in Fig. 1 has a multi-layer structure and includes a substrate 8, an anode 2, a hole injection layer 3, a hole transport layer 6, an emitting layer 1, an electron transport layer 7, an electron injection layer 5, and a cathode 4, in this order.
[0098] (Light Emitting Layer) The light-emitting layer may be made of light-emitting materials such as low molecular weight compounds, polymers, and dendrimers. Polymers are preferred because they are highly soluble in solvents and suitable for coating methods. Light-emitting materials include fluorescent materials, phosphorescent materials, and thermally activated delayed fluorescent materials (TADF).
[0099] Examples of fluorescent materials include low molecular weight compounds such as perylene, coumarin, rubrene, quinacridone, stilbene, dyes for dye lasers, aluminum complexes, and derivatives thereof; polymers such as polyfluorene, polyphenylene, polyphenylenevinylene, polyvinylcarbazole, fluorene-benzothiadiazole copolymer, fluorene-triphenylamine copolymer, and derivatives thereof; and mixtures of these.
[0100] As the phosphorescent material, metal complexes containing metals such as Ir and Pt can be used. As an Ir complex, for example, FIr(pic) (iridium(III)bis[(4,6-difluorophenyl)-pyridinate-N,C], which emits blue light, can be used. 2 ]picolinate), which emits green light, Ir(ppy)3 (factris(2-phenylpyridine)iridium), which emits red light, and (btp)2Ir(acac) (bis[2-(2'-benzo[4,5-α]thienyl)pyridinato-N,C 3 ]iridium(acetylacetonate), Ir(piq)3 (tris(1-phenylisoquinoline)iridium), etc. Examples of Pt complexes include PtOEP (2,3,7,8,12,13,17,18-octaethyl-21H,23H-phorphine platinum) which emits red light, etc.
[0101] When the light-emitting layer contains a phosphorescent material, it is preferable that the light-emitting layer further contains a host material in addition to the phosphorescent material. As the host material, a low molecular weight compound, a polymer, or a dendrimer can be used. As the low molecular weight compound, for example, CBP (4,4'-bis(9H-carbazol-9-yl)biphenyl), mCP (1,3-bis(9-carbazolyl)benzene), CDBP (4,4'-bis(carbazol-9-yl)-2,2'-dimethylbiphenyl), their derivatives, etc., and as the polymer, the organic electronic material, polyvinylcarbazole, polyphenylene, polyfluorene, their derivatives, etc. can be mentioned.
[0102] Examples of thermally activated delayed fluorescence materials include PIC-TRZ (2-biphenyl-4,6-bis(12-phenylindolo[2,3-a]carbazol-11-yl)-1,3,5-triazine), Spiro-CN (2',7'-bis(di-P-tolylamino)-9,9'-spirobifluorene-s,7-dicarbonitrile), and CC2TA (2,4-bis{3-(9H-carbazol-9 -yl)-9H-carbazol-9-yl}-6-phenyl-1,3,5-triazine), CZ-PS(9,9'-(4,4'-sulfonylbis(4,1-phenylene))bis(3,6-di- tert-butyl-9H-carbazole)), 4CzPN(3,4,5,6-tetra(9H-carbazol-9-yl)phthalonitrile), HAP-3TPA(4,4',4''-(1,3,3a 1 ,4,6,7,9-heptaazaphenalene-2,5,8-triyl)tris(N,N-bis(4-(tert-butyl)phenyl)aniline)), 4CzIPN(1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene), and other compounds.
[0103] (hole injection layer, hole transport layer) The organic layer is preferably used as at least one of a hole injection layer and a hole transport layer. As described above, these layers can be easily formed by using an ink composition containing an organic electronic material and a solvent.
[0104] When the organic EL element has the organic layer as a hole injection layer and further has a hole transport layer, a known material can be used for the hole transport layer. When the organic EL element has the organic layer as a hole transport layer and further has a hole injection layer, a known material can be used for the hole injection layer. Both the hole injection layer and the hole transport layer may be the organic layer. Examples of known materials include aromatic amine compounds (e.g., aromatic diamines such as N,N'-di(naphthalene-1-yl)-N,N'-diphenyl-benzidine (α-NPD)), phthalocyanine compounds, and thiophene compounds (e.g., thiophene conductive polymers such as poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS)).
[0105] When the hole transport layer is an organic layer with a changed solubility, it is possible to easily form a light emitting layer thereon by a wet process. In this case, the polymerization initiator may be contained in the organic layer that is the hole transport layer, or in the organic layer below the hole transport layer.
[0106] (electron transport layer, electron injection layer) Examples of materials used for the electron transport layer and the electron injection layer include phenanthroline derivatives, bipyridine derivatives, nitro-substituted fluorene derivatives, diphenylquinone derivatives, thiopyran dioxide derivatives, condensed ring tetracarboxylic acid anhydrides such as naphthalene and perylene, carbodiimides, fluorenylidenemethane derivatives, anthraquinodimethane and anthrone derivatives, oxadiazole derivatives, thiadiazole derivatives, benzimidazole derivatives, quinoxaline derivatives, aluminum complexes, etc. The organic electronic materials described above can also be used.
[0107] (cathode) As the cathode material, for example, a metal or a metal alloy such as Li, Ca, Mg, Al, In, Cs, Ba, Mg / Ag, LiF, or CsF can be used.
[0108] (anode) The anode material may be, for example, a metal (e.g., Au) or another material having electrical conductivity, such as an oxide (e.g., ITO: indium oxide / tin oxide) or a conductive polymer (e.g., polythiophene-polystyrene sulfonate mixture (PEDOT:PSS)).
[0109] (substrate) The substrate may be made of glass, plastic, etc. The substrate is preferably transparent and flexible. Quartz glass, resin film, etc. are preferably used.
[0110] The resin film is preferably a light-transmitting resin film, such as a film mainly composed of polyethylene terephthalate, polyethylene naphthalate, polyethersulfone, polyetherimide, polyetheretherketone, polyphenylene sulfide, polyarylate, polyimide, polycarbonate, cellulose triacetate, cellulose acetate propionate, or the like.
[0111] When a resin film is used, the resin film may be coated with an inorganic material such as silicon oxide or silicon nitride in order to suppress the transmission of water vapor, oxygen, and the like.
[0112] (Sealing) The organic EL element may be sealed in order to reduce the influence of the outside air and extend the life. Materials used for sealing include glass, epoxy resin, acrylic resin, plastic films such as polyethylene terephthalate and polyethylene naphthalate, and inorganic materials such as silicon oxide and silicon nitride, but are not limited thereto. The sealing method is also not particularly limited, and can be performed by a known method.
[0113] (Emitting color) The color of the emitted light from the organic EL element is not particularly limited. A white organic EL element is preferable because it can be used in various lighting fixtures such as home lighting, car lighting, clocks, and liquid crystal backlights.
[0114] A method for forming a white organic EL element can be a method in which multiple luminescent materials are used to simultaneously emit multiple luminescent colors and mix the colors. The combination of multiple luminescent colors is not particularly limited, but includes a combination containing three luminescent maximum wavelengths of blue, green, and red, and a combination containing two luminescent maximum wavelengths of blue and yellow, yellow-green and orange, etc. The luminescent color can be controlled by adjusting the type and amount of the luminescent material.
[0115] <5> Display element, lighting device, display device One embodiment of the present invention relates to a display device including the organic EL element. For example, a color display device can be obtained by using organic EL elements as elements corresponding to each pixel of red, green, and blue (RGB). There are two methods for forming an image: a simple matrix type in which individual organic EL elements arranged on a panel are directly driven by electrodes arranged in a matrix, and an active matrix type in which thin film transistors are arranged in each element to drive it.
[0116] Moreover, one embodiment of the present invention relates to a lighting device including the organic EL element.Furthermore, one embodiment of the present invention relates to a display device including the lighting device and a liquid crystal element as a display means.For example, the display device can be a display device using the lighting device as a backlight and a known liquid crystal element as a display means, i.e., a liquid crystal display device. EXAMPLES
[0117] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples and includes various embodiments.
[0118] <1> Charge-transporting polymer The raw material monomers used to synthesize the charge transporting polymers in the following Examples and Comparative Examples are shown below.
[0119] [ka]
[0120] [ka]
[0121] [ka]
[0122] Example 1 (1) Synthesis of charge-transporting polymer A reaction vessel equipped with a Dimroth condenser and a stirring function was prepared, and an oil bath was placed so that it could move forward and backward relative to the reaction vessel. The following components were added to the reaction vessel, whose atmosphere had been replaced with nitrogen, while nitrogen was injected, and a nitrogen gas supply device was connected to the tip of the Dimroth condenser to create a reaction environment in a nitrogen atmosphere. Starting monomers: Monomer A1 (1285 mg, 2.67 mmol), Monomer B1 (1027 mg, 5.00 mmol), Monomer C1 (370 mg, 2.00 mmol) Organic solvent (toluene): Dehydrated toluene stored under nitrogen atmosphere, Fujifilm Wako Pure Chemical Industries, Ltd., 31.0 mL Base: sodium t-butoxide, manufactured by Tokyo Chemical Industry Co., Ltd., 1442 mg (3.0 equivalents based on the monomer B1 having an amino group) Catalyst: Pd[P(t-Bu)3]2, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 102 mg (4.0 mol % based on the monomer B1 having an amino group) Additive: P(t-Bu)3·HBF4, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 58 mg (4.0 mol % based on the monomer B1 having an amino group)
[0123] Next, the reaction vessel was heated in an oil bath (bath temperature: 120° C.) to a temperature at which the organic solvent in the reaction vessel refluxed, and the reaction was carried out for 2 hours with stirring. After the above reaction, the temperature of the reaction mixture in the reaction vessel was lowered to room temperature, the obtained organic layer was washed with water, and reprecipitation was performed using methanol-water (9:1), and the resulting precipitate was suction filtered. Ethyl acetate was added to the obtained precipitate, and the precipitate was stirred for 15 minutes while being heated to 60°C in an oil bath, and the precipitate was washed with ethyl acetate. After washing, the washed precipitate was collected by suction filtration. This washed precipitate was washed once more with ethyl acetate in the same manner as above, and the remaining monomers and reactants soluble in ethyl acetate in the precipitate were removed. Next, the precipitate washed with ethyl acetate was dried under reduced pressure to obtain a charge transporting polymer (light yellow powder). Proton nuclear magnetic resonance ( 1 By measuring the 1 H-NMR spectrum, it was confirmed that the polymer had a structure represented by the following formula (IA-1) obtained by polycondensation of monomers A1, B1, and C1.
[0124] [ka]
[0125] The polymer yield was 70%, the weight average molecular weight (Mw) was 35,400, the number average molecular weight (Mn) was 9,800, and the molecular weight distribution Mw / Mn was 3.6. In addition, 1 The H-NMR spectrum was measured using an AVANCE-600 NMR spectrometer manufactured by Bruker. The Mw and Mn were measured using a Prominence GPC system manufactured by Shimadzu Corporation. The Mw and Mn were measured by gel permeation chromatography (GPC) using a styrene gel column, calibrated with standard polystyrene at 40° C., and then tetrahydrofuran was used as the eluent. The measurement conditions were as follows. The same applies to the examples described below.
[0126] Liquid delivery pump: L-6050 Hitachi High-Technologies Corporation UV-Vis Detector: L-3000 Hitachi High-Technologies Corporation Column: Gelpack (registered trademark) GL-A160S / GL-A150S, Resonac Inc. Eluent: THF (for HPLC, no stabilizers) Wako Pure Chemical Industries, Ltd. Flow rate: 1ml / min Column temperature: room temperature Molecular weight standard: Standard polystyrene
[0127] The amount of impurities in the polymer was measured according to the following method, and the results are shown in Table 2. (Method of analyzing impurity content) The contents of palladium (Pd), Br and Cl in each polymer were measured using an energy dispersive X-ray fluorescence analyzer (hereinafter referred to as EDX) under the following measurement conditions. Equipment: Shimadzu, EDX-7000 X-ray tube: Rh target Atmosphere:Atmospheric Measurement time (sec): Pd: 600, Br: 100, Cl: 1000 Analysis range (keV): Pd: 20.72-21.52, Br: 11.66-12.16, Cl: 2.42-2.82
[0128] Example 2 Polymers were prepared in the same manner as in Example 1, except that the raw material monomers and their blending amounts were changed as shown in Table 1. Various measurements were carried out on the obtained polymers in the same manner as in Example 1. The results are shown in Table 2.
[0129] Example 3 A reaction vessel equipped with a Dimroth condenser and a stirring function was prepared, and an oil bath was placed so that it could move forward and backward relative to the reaction vessel. The following components were added to the reaction vessel, whose atmosphere had been replaced with nitrogen, while nitrogen was injected, and a nitrogen gas supply device was connected to the tip of the Dimroth condenser to create a reaction environment in a nitrogen atmosphere. Starting monomers: Monomer A1 (1285 mg, 2.67 mmol), Monomer B3 (886 mg, 5.00 mmol), Monomer C1 (370 mg, 2.00 mmol) Organic solvent (toluene): Dehydrated toluene stored under nitrogen atmosphere, Fujifilm Wako Pure Chemical Industries, Ltd., 27.8 mL Base: sodium t-butoxide, manufactured by Tokyo Chemical Industry Co., Ltd., 1442 mg (3.0 equivalents based on the monomer B3 having an amino group) Catalyst: Pd[P(t-Bu)3]2, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 102 mg (4.0 mol % based on the monomer B3 having an amino group) Additive: P(t-Bu)3·HBF4, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 58 mg (4.0 mol % based on the amount of monomer B3 having an amino group)
[0130] Next, the reaction vessel was heated in an oil bath (bath temperature: 120° C.) to a temperature at which the organic solvent in the reaction vessel refluxed, and the reaction was carried out for 2 hours with stirring. After the above reaction, the temperature of the reaction mixture in the reaction vessel was lowered to room temperature, and 10 mL of an aqueous solution of sodium N,N-diethyldithiocarbamate trihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) adjusted to 0.1 mol / L was added and stirred. The resulting suspended solution was reprecipitated using methanol-water (9:1), and the resulting precipitate was suction filtered. Ethyl acetate was added to the resulting precipitate, and the mixture was stirred for 15 minutes while being heated to 60°C in an oil bath, and the precipitate was washed with ethyl acetate. After washing, the washed precipitate was collected by suction filtration.
[0131] The washed precipitate was washed once more with ethyl acetate in the same manner as described above to remove the remaining monomers and ethyl acetate-soluble reactants in the precipitate. The precipitate washed with ethyl acetate was then dried under reduced pressure to obtain a polymer (light yellow powder). The yield of the polymer was 72%, the weight average molecular weight (Mw) was 37,100, the number average molecular weight (Mn) was 12,500, and the molecular weight distribution Mw / Mn was 3.0. The amount of impurities in the polymer was measured in the same manner as in Example 1. The results are shown in Table 2.
[0132] (Examples 4 to 12) Polymers were prepared in the same manner as in Example 3, except that the synthesis conditions, such as the raw material monomers, blend amounts, and catalysts, were changed as shown in Table 1. In Examples 8, 10, and 11, washing with ethyl acetate was not performed because an oily precipitate was generated during reprecipitation. Therefore, the yields were not calculated. Various measurements were performed on the obtained polymers in the same manner as in Example 1. The results are shown in Table 2.
[0133] Comparative Example 1 In Comparative Example 1, a charge transporting polymer was prepared according to the Suzuki-Miyaura cross-coupling method. Specifically, the polymer was prepared as follows. (Preparation of Pd catalyst solution) In a glove box under a nitrogen atmosphere, tris(dibenzylideneacetone)dipalladium (0.183 g, 0.200 mmol) was weighed into a sample container at room temperature, toluene (40.00 mL) was added, and the mixture was stirred for 10 minutes. Similarly, tris(tert-butyl)phosphine (0.324 g, 1.600 mmol) was weighed into a different sample container, toluene (10.00 ml) was added, and the mixture was stirred for 10 minutes. These solutions were mixed and stirred at room temperature for 10 minutes to obtain a Pd catalyst solution. All solvents used in the preparation of the Pd catalyst solution were degassed for 30 minutes or more under a nitrogen atmosphere using nitrogen bubbles at 1 L / min, and the oxygen concentration was 0.5% O2 or less.
[0134] (Polymer preparation and purification) A reaction vessel equipped with a Dimroth condenser and a stirring function was prepared, and an oil bath was placed so that it could move forward and backward relative to the reaction vessel. The raw material monomers, base, and additive components listed below were each added to the reaction vessel, which had been replaced with nitrogen, while nitrogen was being injected, and a nitrogen gas supply device was connected to the tip of the Dimroth condenser, and the materials were dissolved at 60°C. Next, the catalysts listed below were added to the reaction vessel, which was heated in an oil bath (bath temperature 120°C) to a temperature at which the organic solvent refluxed, and the reaction was carried out for 2 hours while stirring. Starting monomers: Monomer A1 (964 mg, 2.00 mmol), Monomer B4 (2767 mg, 5.00 mmol), Monomer C1 (740 mg, 4.00 mmol) Organic solvent (toluene): Dehydrated toluene stored under nitrogen atmosphere, Fujifilm Wako Pure Chemical Industries, Ltd., 45.6 mL Base: 3.0 mol% potassium hydroxide aqueous solution (7.79 mL) Catalyst: Pd catalyst solution prepared above (1.01 mL) Additive: Methyltri-n-octylammonium chloride (0.034 g, Aliquat336 / Alfa Aesar)
[0135] Next, the reaction vessel was heated in an oil bath (bath temperature: 120° C.) to a temperature at which the organic solvent in the reaction vessel refluxed, and the reaction was carried out for 2 hours with stirring. After the above reaction, the temperature of the reaction mixture in the reaction vessel was lowered to room temperature, and 10 mL of an aqueous solution of sodium N,N-diethyldithiocarbamate trihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) adjusted to 0.1 mol / L was added and stirred. The separated organic phase was reprecipitated using methanol-water (9:1), and the resulting precipitate was suction filtered. Ethyl acetate was added to the resulting precipitate, and the mixture was stirred for 15 minutes while heating to 60°C in an oil bath, and the precipitate was washed with ethyl acetate. After washing, the washed precipitate was collected by suction filtration. This washed precipitate was washed once more with ethyl acetate in the same manner as above, and the remaining monomers and reactants soluble in ethyl acetate in the precipitate were removed. The precipitate washed with ethyl acetate was then dried under reduced pressure to obtain a polymer (light yellow powder). Proton nuclear magnetic resonance of polymers ( 1 By measuring the 1 H-NMR spectrum, it was confirmed that the polymer had a structure obtained by polycondensation of the monomers A1, B4 and C1 (a structure represented by the following formula (II) described later).
[0136] The yield of the polymer was 50%, the weight average molecular weight (Mw) was 43,400, the number average molecular weight (Mn) was 13,300, and the molecular weight distribution Mw / Mn was 3.3. The amount of impurities in the polymer was measured in the same manner as in Example 1. The results are shown in Table 2. In Table 2, "ND" stands for Not Detected, which means that the amount was below the detection limit.
[0137] [Table 1]
[0138] The details of the catalysts listed in Table 1 are as follows: Pd[P(t-Bu)3]2: Bis(tri-tert-butylphosphine)palladium(0), manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. XphosPd G2: Product name of Aldrich Co., Ltd. Chloro(2-dicyclohexylphosphino-2',4',6'-triisopropyl-1,1'-biphenyl)[2-(2'-amino-1,1'-biphenyl)]palladium PdCl2(dtbpf): [1,1'-bis(di-tert-butylphosphino)ferrocene]dichloropalladium(II), manufactured by Aldrich Co. PdCl2(amphos)2: bis(di-tert-butyl(4-dimethylaminophenyl)phosphine)dichloropalladium(II), manufactured by Aldrich Co., Ltd. Umicore CX-31: [1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene]chloro[3-phenylallyl]palladium(II), manufactured by Aldrich Corporation. Umicore CX-32: [1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene]chloro[3-phenylallyl]palladium(II), manufactured by Aldrich Corporation. PdArBrP(t-Bu)3: A compound represented by the following formula (2) (prepared by reacting tris(dibenzylideneacetone)dipalladium(0) (manufactured by Tokyo Chemical Industry Co., Ltd.), o-bromotoluene (manufactured by Tokyo Chemical Industry Co., Ltd.), and tri-tert-butylphosphine (manufactured by Tokyo Chemical Industry Co., Ltd.)). [ka]
[0139] [Table 2]
[0140] <2> Organic Electronics Materials Ink compositions were prepared as organic electronic materials as follows, using the polymers synthesized in Example 5 and Comparative Example 1. The polymer synthesized in Example 5 has a structure represented by the following formula (IA-2), and the polymer synthesized in Comparative Example 1 has a structure represented by the following formula (II).
[0141] [ka]
[0142] [ka]
[0143] The polymers (50.0 mg) obtained in Example 5 and Comparative Example 1 and the ionic compound (0.5 mg) shown below were weighed out and placed in 9 mL screw tubes, and toluene (2449.5 mg) was added thereto to dissolve, thereby preparing ink compositions.
[0144] [ka]
[0145] <3> Preparation and evaluation of HOD (1) Fabrication of hole-only device (HOD) Using the organic electronic materials (ink compositions) of Example 5 and Comparative Example 1 prepared above, HODs were produced and evaluated as follows. Each ink composition was filtered using a PTFE filter (pore size 0.2 μm). The filtered ink composition was used to form a film on a quartz substrate (length 22 mm × width 29 mm × thickness 0.7 mm, hereinafter referred to as ITO substrate) patterned to a width of 1.6 mm, using a spin coater. Then, the substrate was heated at 230° C. for 30 minutes in a nitrogen atmosphere to form an organic layer with a thickness of 60 nm on the ITO substrate. The ITO substrates having the organic layers prepared as described above were transferred into a vacuum deposition machine, and aluminum (Al) was deposited to a thickness of 100 nm on the organic layers by a deposition method. A sealing process was then performed to prepare hole-only devices (hereinafter referred to as HODs) for evaluating electrical conductivity. FIG. 2 is a schematic cross-sectional view showing the structure of an HOD. As shown in FIG. 2, the HOD is a laminate having an anode 12, an organic layer (hole injection layer) 13, and a cathode 14 in this order on a substrate 11, and a sealing process (not shown) is performed to surround the laminate.
[0146] (2) Evaluation of HOD (2-1) Evaluation of electrical conductivity A voltage was applied to the HODs for evaluating the conductivity of Example 5 and Comparative Example 1, which were previously prepared, to confirm the conductivity (hole injection function) when a voltage was applied. Furthermore, measurements were performed by changing the applied voltage to the HODs of Example 5 and Comparative Example 1. Graphs of voltage-current density curves when a voltage was applied to each HOD prepared in Example 5 and Comparative Example 1 are shown in FIG. These results are summarized in Table 3.
[0147] [Table 3]
[0148] In Table 3, details of items (1) to (3) are as follows: (1) Checking electrical conductivity A: Conductive B: Non-conductive (2) Conductivity rating 1 The applied voltage was changed and the current density was 0.1 mA / cm 2 The voltage at this time was measured. (3) Conductivity rating 2 The applied voltage was changed to a current density of 20 mA / cm 2 The voltage at this time was measured.
[0149] (2-2) Evaluation of hole density Using the HODs for evaluating electrical conductivity of Example 5 and Comparative Example 1 prepared above, the hole density was evaluated by the method described below. (Evaluation method) Information on the hole density can be obtained by impedance spectroscopy (hereinafter, IS method). Specifically, the ITO and Al electrodes of the HODs of Example 5 and Comparative Example 1 were connected to an LCR meter under the following conditions. Then, the frequency dependence of the impedance of the HODs was measured and analyzed, and the hole density was calculated.
[0150] <Measurement conditions> Measuring device: LCR meter (NF Circuit Block, ZM2376) Frequency range: 0.1Hz~5.5MHz AC amplitude: 100mV
[0151] <How to calculate hole density> Assuming that the organic layer has an electrical resistance "R" and a capacitance "C", and approximating it with a parallel circuit model, the complex impedances "Z1 (Equation 1)" and "Z2 (Equation 2)" of the circuit model are obtained as shown below.
[0152]
number
[0153] In addition, in the analysis of the frequency dependency of impedance, the moduli "M1 (Equation 3)" and "M2 (Equation 4)" were used as shown below.
[0154]
number
[0155] The resistance and capacitance of each organic layer can be obtained by the relationship between the observed peaks and heights of "M1" and "M2" as shown in (Formula 6) and (Formula 7) below.
[0156]
number
[0157] In HOD doped with holes by an ionic compound (polymerization initiator), the holes move so that the HOMO level matches the work function of the metal at the interface with the metal, forming a depletion layer with a thickness of "d". At this time, the capacitance "C" and thickness "d" of the depletion layer are given by (Equation 7) as shown below.
[0158]
number
[0159] Furthermore, if the thickness of the depletion layer "d" is the space charge density (anion density) in the depletion layer "N", then when no bias voltage is applied, it is expressed by the following (Equation 8). Here, since the anion density "N" and the hole density are equal, the hole density can be calculated using (Equation 8).
[0160]
number
[0161] (Evaluation results of hole density) According to the above method, the hole density of the HODs prepared using the organic electronic materials (ink compositions) of Example 5 and Comparative Example 1 was calculated. The hole density obtained using the ink composition of Comparative Example 1 is set as the reference (100), and the hole density obtained using the ink composition of Example 5 is shown in Table 4.
[0162] [Table 4]
[0163] From the above, it is understood that the organic electronic material (ink composition) containing the charge transporting polymer according to the present invention can easily form an organic layer capable of improving the electrical conductivity and hole density. [Explanation of symbols]
[0164] 1. Light-emitting layer 2 Anode 3. Hole injection layer 4 cathode 5 Electron injection layer 6. Hole transport layer 7 Electron transport layer 11 Substrate 12 Anode 13 Hole injection layer 14 Cathode
Claims
1. The organic electronic material comprises a charge-transporting polymer having a weight-average molecular weight of 900 to 500,000, the charge-transporting polymer comprising a trivalent structural unit represented by the following formula (a) and a divalent structural unit represented by the following formula (b), and having at least a structure represented by the following formula (I) in which at least one bond in the trivalent structural unit is directly bonded to at least one bond in the divalent structural unit: 【Chemistry 1】 【Chemistry 2】 [In the formula, Ar represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.]
2. 2. The organic electronic material according to claim 1, wherein in the structure represented by formula (I), Ar is a group represented by the following general formula: 【Chemistry 3】 [In the formula, R 1 is an alkyl group having 1 to 8 carbon atoms, and a is 0 or an integer of 1 to 5.
3. 3. The organic electronic material according to claim 1, wherein the structure represented by formula (I) includes a structure represented by the following formula (I-2) or (I-3): 【Chemistry 4】 [In the formula, each Ar independently represents a substituted or unsubstituted aryl group, and * represents a bond to another structure.]
4. The organic electronic material according to claim 1 or 2, wherein the charge transporting polymer comprises a structure represented by the following formula (IA): 【Chemistry 5】 [In the formula, Ar represents a substituted or unsubstituted aryl group, and n is an integer of 2 or more.]
5. The organic electronic material according to claim 1 or 2, wherein the charge transporting polymer further has a monovalent structural unit represented by the following formula (c): 【Chemistry 6】 [In the formula, R 2 is an alkyl group having 1 to 8 carbon atoms, and b is 0 or an integer of 1 to 5.
6. The organic electronic material according to claim 1 or 2, further comprising a solvent.
7. An organic layer formed by using the organic electronic material according to claim 6 .
8. An organic electronic device comprising the organic layer according to claim 7.
9. An organic electroluminescent device comprising the organic layer according to claim 7.
10. A display device comprising the organic electroluminescence device according to claim 9.
11. A lighting device comprising the organic electroluminescence element according to claim 9.
12. A display device comprising the lighting device according to claim 11 and a liquid crystal element as a display means.
Citation Information
Patent Citations
Organic electronic material, organic electronic device and organic electroluminescent device
WO2008010487A1